Konfigurale Auswertung von Daten aus Prätest-Posttest Kontrollgruppen Designs - Stemmler, Mark; Masendorf, Friedrich (Zeitschrift für Klinische Psychologie, Psychiatrie und Psychotherapie, 1998)
Examines methods of configural frequency analysis (CFA) for treatment evaluation in multivariate pretest–posttest designs. Three CFA methods are proposed: prediction CFA, interaction CFA and generalized unary hypothesis analysis. These methods are compared and evaluated. Data from a prior experiment are used to assess the effect of training methods on calculation and learning methods in learning disabled children using CFA methods. The effect on pretest–posttest designs are assessed using numerical analysis.
Keywords: Experimental Design; Multivariate Analysis; Treatment Effectiveness Evaluation; Methodology; Pretesting